Comments on “The surgical approach of late-onset tracheoesophageal fistula in a tracheostomized COVID-19 patient” - Dario Amore; Marco Rispoli; Umberto Caterino; Dino Casazza; Pasquale Imitazione; Alessandro Saglia; Cristiano Cesaro (Monaldi Archives for Chest Disease, 2023)
Dear Editor,